NEKROLOGI RPEiS 75, 2013, z. 1 - Olejniczak, Adam; Panowicz-Lipska, Janina; Szwarc, Andrzej J. (Wydział Prawa i Administracji UAM, 2013)
Profesor dr, dr h.c. Zbigniew Radwański (1924-2012) (Adam Ol e j n i c z a k, Janina P a n o w i c z - L i p s k a), s. 311-317; Prof. dr hab. Aleksander Tobis (1932-2012) (Andrzej J. S z w a r c), s. 317-319
OBITUARIES 75 (1), 2013